Peripheralisation: A Politics of Place, Affect, Perception and Representation. Issue 2 (7th March 2017) - Willett, Joanie; Lang, Thilo
Abstract: Recently scholars have started to consider the persistence of peripheries in relation to how they are represented by others outside of the region. Drawing on Foucauldian knowledge/power processes and forms of 'internal colonialism', powerful core regions construct and reconstruct knowledge about peripheries as a weaker 'other'. However this denies agency to passive, peripheral 'victims', compromising their capacity to contest their peripherality. We challenge this using Deleuze and Guattari's assemblages and the concepts of affect and perception to develop a conceptualisation of power which allows agency to weaker entities. This enables us to develop better tools for improving peripheral development. We use an innovative Public Engagement research method and a case‐study of Cornwall in the South West of the UK to consider an alternative model with regards to how ideas become accepted and adopted. We claim that analyses of the relationships between core and peripheral regions need to understand the complex cultural assemblages behind regional identities, because this helps us to explore the sites of possibility which offer space for development.